Summertime [videorecording (DVD)] - Lean, David, 1908-1991; Lean, David, 1908-1991; Hepburn, Katharine, 1907-2003; Brazzi, Rossano, 1916-1994; McGavin, Darren, 1922-2006; Laurents, Arthur (Criterion collection, 1998)
The story of a witty but lonely secretary who takes a vacation in Venice, hoping to fall in love. She does - with a very handsome but very married Italian man.